Review article: delivering precision oncology in intermediate‐stage liver cancer. Issue 12 (25th April 2017) - Pinato, D. J.; Howell, J.; Ramaswami, R.; Sharma, R.
Summary: Background: Intermediate‐stage hepatocellular carcinoma (HCC), for which trans‐arterial chemoembolization (TACE) constitutes the standard of care, is a patient subgroup with significant heterogeneity in clinical outcome. Sources of variation relate to differences in tumour burden, hepatic reserve, ethnicity and treatment modalities. Increasing research efforts have been dedicated to minimise the clinical diversity of this patient population and enhance optimal provision of treatment. Aim: To comprehensively review the diverse prognostic models that have been proposed to refine the prognostic prediction of patients with HCC undergoing TACE. Results: A number of prognostic algorithms (HAP, ART, ABCR score and many others) have shown potential to address the clinical heterogeneity characterising patients with intermediate‐stage HCC and facilitate early identification of patients with poor prognostic features in whom alternative treatments or best supportive care might be more appropriate than TACE. Conclusions: While an improved characterisation of intermediate‐stage HCC is a highly important clinical aim, current evidence suggests that novel prognostic algorithms in this patient population may offer potential benefits but non‐negligible challenges in the provision of TACE. This review summarises the currently available evidence to facilitate the development of precision oncology in intermediate‐stage HCC.